2013
DOI: 10.1111/bdi.12064
|View full text |Cite
|
Sign up to set email alerts
|

The immature dentate gyrus represents a shared phenotype of mouse models of epilepsy and psychiatric disease

Abstract: ObjectivesThere is accumulating evidence to suggest psychiatric disorders, such as bipolar disorder and schizophrenia, share common etiologies, pathophysiologies, genetics, and drug responses with many of the epilepsies. Here, we explored overlaps in cellular/molecular, electrophysiological, and behavioral phenotypes between putative mouse models of bipolar disorder/schizophrenia and epilepsy. We tested the hypothesis that an immature dentate gyrus (iDG), whose association with psychosis in patients has recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 54 publications
(81 reference statements)
6
52
0
Order By: Relevance
“…As these findings are similar to ours, it supports a common theme, that ectopic mossy fiber projection may contribute to seizure generation by inducing hyperactivity in hippocampus. This hypothesis is supported by previous findings that identify decreased seizure threshold in ␣-CaMKII hKO mice [15]. Further, mossy fibers undergo continuous turnover, even in adulthood [23], and some studies have suggested that the newly-generated granule cells play an important role in pattern separation task [24], which is often disturbed in psychiatric patients [25].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…As these findings are similar to ours, it supports a common theme, that ectopic mossy fiber projection may contribute to seizure generation by inducing hyperactivity in hippocampus. This hypothesis is supported by previous findings that identify decreased seizure threshold in ␣-CaMKII hKO mice [15]. Further, mossy fibers undergo continuous turnover, even in adulthood [23], and some studies have suggested that the newly-generated granule cells play an important role in pattern separation task [24], which is often disturbed in psychiatric patients [25].…”
Section: Discussionsupporting
confidence: 73%
“…Previously-described ␣-CaMKII hKO mice, licensed from Massachusetts Institute of Technology [14,15], were maintained on a C57BL/6 background at Hilltop Labs (Scottdale, PA, USA). Adult mice (3-9 months old C57BL/6 wild type (WT) and ␣-CaMKII hKO littermates) were maintained on a 12 h on, 12 h off light cycle.…”
Section: Animalsmentioning
confidence: 99%
“…Several studies have recently identified the 'immature dentate gyrus' (iDG) as a conserved pathophysiological alteration that is found in neuropsychiatric disorders, including schizophrenia and bipolar disorder (Reif et al, 2006;Yamasaki et al, 2008;Walton et al, 2012;Hagihara et al, 2013;Shin et al, 2013). The observation of iDG was first reported in mice with a heterozygous mutation in the α-calcium/calmodulindependent protein kinase II (Camk2a) gene.…”
Section: Box 1 Immature Dentate Gyrus In Neuropsychiatric Diseasesmentioning
confidence: 99%
“…Finally, hippocampal neurogenesis deficits have been linked to cognitive defects characteristic of depression (Patricio et al, 2013), impairment in early Alzheimer's disease pathology (Demars et al, 2010;Faure et al, 2011;Mu and Gage, 2011;Rodriguez et al, 2011), bipolar disorder (Valvezan and Klein, 2012;Walton et al, 2012) and schizophrenia (SCZD) (Tamminga et al, 2010;Walton et al, 2012;Hagihara et al, 2013). More specifically, alterations in DG granule neuron maturation have been implicated in the etiology and pathogenesis of schizophrenia and bipolar disorder (see Box 1; Reif et al, 2006;Yamasaki et al, 2008;Walton et al, 2012;Hagihara et al, 2013;Shin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Number of entries to the arm were measured and taken to reflect the level of anxiety. The alternation rate was attributed to working memory [18].…”
Section: Y-maze Testmentioning
confidence: 99%